THE EFFECT OF PROVISION OF CHICKEN MANURE AND N-FERTILIZER ON THE GROWTH OF PAKCOY PLANTS (Brassica rapa L.) USING THE PARALON VERTICULTURE SYSTEM - Fenty Maimunah Simbolon; Murni Sari Rahayu; Yayuk Purwaningrum; Muhamad Zepri (PT Inovasi Pratama Internasional, 2019)
The research was conducted in the greenhouse of the Faculty of Agriculture, Islamic University of North Sumatra, Jl. Eka Warni, Medan Johor District, Medan City. With a height of place ± 25 masl with flat tofografi. This research was conducted in April 2017 until June 2017. The aim of this research is to know the effect of chicken manure and N fertilizer on growth and production of mustard pakcoy plant with parallon vertikultur system. The design of this study used a Completely Randomized Design (CRD) Factorial consisting of two factors and repeated three times. The first factor is the provision of chicken coop (A) which consists of 4 levels, namely: A0 = 0 g / parallon (Control); A1 = 1000 g / parallon; A2 = 2000 g / parallon; A3 = 3000 g / parallon. The second factor is N (N) fertilizer consisting of 4 levels, namely: N0 = 0 g / parallon (Control); N1 = 1.8g / plant; N2 = 3.7g / plant; N3 = 5.6g / plant. The results showed that chicken manure gave a very significant effect on all parameters observed. The provision of chicken manure has a very significant effect on the parameters of plant height, the number of leaves, the diameter of the cob. The results showed that N fertilizer gave very significant effect on the parameters of plant height, leaf number, diameter of cob. The interaction of chicken manure and N fertilizer gave a very real effect on the diameter of the hump. However, the effect is not significant on the parameters of plant height, number of leaves.